2016
DOI: 10.1007/s10729-016-9376-0
|View full text |Cite
|
Sign up to set email alerts
|

A widening gap? Static and dynamic performance differences between specialist and general hospitals

Abstract: This paper develops and tests a dynamic model of hospital focus. It does so by tracing the performance trajectories of specialist and general hospitals to identify whether a performance gap exists and whether it widens or shrinks over time. Our longitudinal analyses of all hospital organizations within the English National Health Service (NHS) reveal not only a notable performance gap between specialist and general hospitals in particular with regards to patient satisfaction that widens over time, but also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…In practice, the number of specialized healthcare units, such as single specialty hospitals [7][8][9] and ambulatory surgery centres [10], has grown rapidly. Several empirical studies have also shown that specialized units outperform general hospitals both in cost efficiency [8,11] and in patient satisfaction [12,13]. literature on the link between focus and performance by supporting the notion that hospital focus is an important driver of quality and productivity for routine patients.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In practice, the number of specialized healthcare units, such as single specialty hospitals [7][8][9] and ambulatory surgery centres [10], has grown rapidly. Several empirical studies have also shown that specialized units outperform general hospitals both in cost efficiency [8,11] and in patient satisfaction [12,13]. literature on the link between focus and performance by supporting the notion that hospital focus is an important driver of quality and productivity for routine patients.…”
Section: Introductionmentioning
confidence: 90%
“…In practice, the number of specialized healthcare units, such as single specialty hospitals [ 7 , 8 , 9 ] and ambulatory surgery centres [ 10 ], has grown rapidly. Several empirical studies have also shown that specialized units outperform general hospitals both in cost efficiency [ 8 , 11 ] and in patient satisfaction [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Miller and Adam ( 15 ), Singh ( 29 ), and Bromiley ( 30 ) have commonly used “return on assets” (ROA) to measure the operational performance of firms. Vera et al ( 31 ) also uses ROA as an indicator of hospital financial performance which is frequently used in the hospital sector. Therefore, the research selects ROA as the dependent variable to measure the performance.…”
Section: Methodsmentioning
confidence: 99%
“…Previous literatures have described the concept of slack resources as including “thinking time”, which is particularly important for the improvement of output of healthcare providers as knowledge workers [ 12 ]. Job satisfaction is also one of factors related to individual performance, which has been widely studied, while literature has shown that job satisfaction of hospital staff is also one of the organizational performance indicators of hospitals [ 13 ]. Niskala, et al [ 14 ] has also pointed out that job satisfaction, which is positively correlated with healthcare service performance, has been critical to the functioning of healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The clinicians’ job satisfaction is a key topic for healthcare managers and patients to focus on. Managers can save on the financial costs associated with high clinician turnover by improving job satisfaction [ 15 ], while there is also a positive dynamic relationship between clinicians’ job satisfaction and patient satisfaction [ 13 ]. In addition, there is evidence in the field of health care that job satisfaction is related to slack resources of hospitals, while Choi, et al [ 16 ] has pointed out that the staffing and resources of the department can affect the improvement of job satisfaction of nurses.…”
Section: Introductionmentioning
confidence: 99%